[tex]4tan \theta = 12 - tan^{2} \theta[/tex]
[tex]tan^{2} \theta + 4tan \theta - 12 = 0[/tex]
Let [tex]x = tan \theta[/tex]
[tex]x^{2} + 4x - 12 = 0[/tex]
[tex](x + 6)(x - 2) = 0[/tex]
[tex]x = -6, x = 2[/tex]
[tex]tan \theta = -6, tan \theta = 2[/tex]
Since they both work, then we can write the solutions in general form:
[tex]\theta = n \pi + tan^{-1}(2)[/tex], [tex]n \in Z[/tex]
[tex]\theta = n \pi - tan^{-1}(6)[/tex], [tex]n \in Z[/tex]
Now, these solutions will always satisfy the equation and substituting a whole number in place of n will produce a solution that satisfies the given equation.